Online Interactive through Branded Entertainment Games as Marketing Communication Activities in the Digital Era - Indra Novianto Adibayu Pamungkas; Ariyani, Nafiah (Lingkar Studi Komunikasi (LISKI), 2024)
One-way advertising messages no longer get the attention of the entire audience because of the presence of new technology. Human tendency to reject the message of advertising because his presence appears in the middle of the fun that is being done. Marketers need to think of new ways to keep advertising by getting into the excitement, creating interactions, and spreading messages in an integrated way. Online interactive with the concept of branded entertainment games becomes an effort by marketers to make targets become captive audiences. This research is a qualitative study with an analysis of literature study discourse on online interaction and branding studies. The need for the process of Analysis, design, development, implementation, and evaluation through the concept of ADDIE in interactive online activities through branded entertainment games. The integration of messages needs to be reflected in the product, namely the games themselves, the design of the integration of marketing communication messages and the integration of messages in online interactive. The integration of messages is necessary to make the audience will receive the same message so that it is easy to recognize the brand through marketing communication activities. Marketers need to evaluate each of their marketing activities because digital conditions are fast becoming obsolete with the presence of a newness that appears. Key Word: Branded Entertainment, Game, Digital Marketing, Marketing Communications, Online Interactive